The Right of a Member of Parliament to Cross over to another Party: A Constitutional Perspective - Muhandiram, Niroshika Liyana (University of Colombo, 2015)
Crossing over to another party has become a trend in the political culture of Sri Lanka today. Many crossovers of Members of Parliament (MPs) are incredulous to the public, as such acts negate the sovereignty of the people. The Constitution of 1978 has addressed this issue and Article 99 (13) (a) provides that if an MP ceases by expulsion, his seat in the parliament also becomes vacant. An MP may be expelled from being a member of a political party as a result of crossing over to another party. In a country like Sri Lanka where political parties have become more important, an MP is considered a mere cog in the wheel. However, the proviso of the same article enables the MP to file a petition to the Supreme Court to determine that such expulsion was invalid. This provision protects the autonomy of the MP while protecting the autonomy of the political party. Ultimately, the Supreme Court has the authority to strike the appropriate balance between the discipline of the political party and conscience of the MP. However, the judicial view is changing and differs from time to time. Now, it is considered to be narrowed. For instance, if the political party did not follow the rules of natural justice in the expulsion, the Supreme Court allows an MP to remain in parliament even after leaving his party. The action of the MP was not seriously looked at. Therefore, this research aims to examine the nature of the right of an MP to crossover to another party, focusing attention on the relevant constitutional provisions with decided case law. This paper further investigates prevailing lacunas of Sri Lankan case law. This is a normative research and the methodology of the study is based on legislations and decided case law. The research also points out the way of controlling crossovers by using party constitutions as well as by the judicial interpretation of the Supreme Court. Finally, the conclusion would suggest that the right of an MP to crossing over to another party is not an absolute right.
Keywords: Sovereignty of people, Expulsion, Case Law, Natural Justice